How to re-engage older adults in community sport? Reasons for drop-out and re-engagement. Issue 4 (4th July 2021) - Jenkin, C. R.; Eime, R.M.; van Uffelen, J.G.Z.; Westerbeek, H.
ABSTRACT: Internationally, many sport policies articulate a desire for lifelong participation in sport. However, participation often fluctuates throughout the lifespan and most people drop-out at some stage. Most research on drop-out of sport focuses on children and adolescents, with little attention towards other age groups. The aim of this study was to investigate why adults aged 50+ years dropped out of sport during their life, and how and why they may re-engage later in life. Eight focus groups (n = 49) were conducted, with Australian National Sporting Organisations; adults aged 50+ years, who were either currently involved in sport (e.g. player/volunteer/coach) or not currently involved. The Socio-Ecological Model was used to frame the interview questions, and Leisure Constraints Theory was used to analyse the results. The main themes on drop-out included lack of appropriate playing opportunities; competing priorities; and low priority from sporting organisations. The main themes for re-engagement in sport at an older age included improving physical health; social opportunities, especially with family/friends; and having more leisure time. It is recommended that to re-engage adults aged 50+ years in active sport participation, organisations should focus on providing age appropriate playing opportunities, whilst ensuring that social interaction is an integral focus.